2019
DOI: 10.1021/acs.joc.9b01034
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Decomposition of N-Nitrosoamides in a Self-Assembled Capsule

Abstract: Density functional theory calculations are employed to investigate the mechanism and energies of the decomposition of N-nitrosoamides in the presence of a resorcinarene-based self-assembled nanocapsule. From experiments, it is known that confinement in the capsule inhibits the thermal decomposition of these compounds. N-Nitrosoamides with both aromatic and aliphatic substituents are considered here and the calculations show that, for both kinds, binding to the capsule leads to a significant increase in the ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…As shown in Figure , the barrier for the initial α addition is lowered the most in the presence of the capsule compared to the solution reaction, by approximately 9 kcal mol −1 . To elucidate the origins of this barrier reduction, an energy decomposition analysis was conducted, by following the same procedure as in our previous studies on other reactions in the same capsule (details are given in the Supporting Information) . This analysis showed that the entropic contribution to the barrier is reduced by 4.3 kcal mol −1 due to encapsulation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure , the barrier for the initial α addition is lowered the most in the presence of the capsule compared to the solution reaction, by approximately 9 kcal mol −1 . To elucidate the origins of this barrier reduction, an energy decomposition analysis was conducted, by following the same procedure as in our previous studies on other reactions in the same capsule (details are given in the Supporting Information) . This analysis showed that the entropic contribution to the barrier is reduced by 4.3 kcal mol −1 due to encapsulation.…”
Section: Resultsmentioning
confidence: 99%
“…These include 1) favorable binding of transition states over reactants, 2) binding of substrates in a favorable (preorganized) conformation for reaction, 3) reduction of the entropic penalty, 4) increased concentration of reacting species inside the capsule compared to outside, 5) reactive conformations that are longer‐lived inside the capsule than in solution, 6) electrostatic stabilization of transition states, and 7) elimination of solvent reorganization during the reaction . By using various decomposition schemes, it is possible to partition the energies obtained by the calculations to evaluate the validity of these scenarios, and also to examine sources of various selectivities, as has been done for a number of reactions in confined spaces recently …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculations nicely reproduced the inhibition of the decomposition inside the capsule (Brea et al ., 2019 a , 2019 b ). They confirm that the inhibition is due to an increase in the energy barrier of the 1,3 N → O acyl transfer to form the diazoester intermediate, which is the rate-determining step of the reaction.…”
Section: Rearrangementmentioning
confidence: 99%
“…That is, confinement favors (hypothetical) intermediates that might form inside the capsule but are unexpected in solution. The details of the reaction outside were thoroughly examined by density-functional theory (DFT) calculations (Brea et al ., 2019 a , 2019 b ).…”
Section: Rearrangementmentioning
confidence: 99%